2014
DOI: 10.1002/hipo.22363
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to noise stress: Anxiety, impaired spatial memory, and deteriorated hippocampal plasticity in postnatal life

Abstract: Sound pollution is known as an annoying phenomenon in modern life. Especially, development of organisms during fetal life is more sensitive to environmental tensions. To address a link between the behavioral and electrophysiological aspects of brain function with action of hypothalamus-pituitary-adrenal (HPA) axis in stressed animals, this study was carried out on the male Wistar rats prenatally exposed to sound stress. Groups of pregnant rats were exposed to noise stress for 1, 2, and 4 hour(s). The degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
81
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(94 citation statements)
references
References 54 publications
11
81
0
2
Order By: Relevance
“…This study also found that both sexes exposed to prenatal stress spent less time in the inner zone of the open-field arena during behavioural testing, which supports a role for prenatal stress in increasing vulnerability to disorders leading to anxiety-like behaviours [33,34]. With an increasing number of studies now supporting the striking association between prenatal stress exposure and the development of anxiety-related disorders in offspring [35,36,37], there appears to be a role for the sex of the offspring in determining the severity of the outcomes associated with prenatal stress exposure [33,38,39]. Interestingly, this was not the case in the current study design.…”
Section: Discussionsupporting
confidence: 63%
“…This study also found that both sexes exposed to prenatal stress spent less time in the inner zone of the open-field arena during behavioural testing, which supports a role for prenatal stress in increasing vulnerability to disorders leading to anxiety-like behaviours [33,34]. With an increasing number of studies now supporting the striking association between prenatal stress exposure and the development of anxiety-related disorders in offspring [35,36,37], there appears to be a role for the sex of the offspring in determining the severity of the outcomes associated with prenatal stress exposure [33,38,39]. Interestingly, this was not the case in the current study design.…”
Section: Discussionsupporting
confidence: 63%
“…However, self-grooming can be seen as a de-arousing activity which is increased in anxious rats (Spruijt et al 1992;Kalueff and Tuohimaa 2005;Voigt et al 2005). Although the present design did not allow for analysing anxiety-related behaviour in dams, earlier studies demonstrated that offspring from dams previously exposed to a stress-inducing environment will show stronger responses to anxiogenic stimuli (Plotsky and Meaney 1993;Ladd et al 2000;Wei et al 2010;Maccari et al 2014;Barzegar et al 2015). Alternatively, grooming could also be associated with the significantly increased feeding as observed in the dams in the present study.…”
Section: Discussionmentioning
confidence: 49%
“…Many preclinical studies have attempted to find experimental support for these observations but the results are not consistent. Prenatal stress was shown to slow the rate of acquisition of spatial memory in adult male rats [4,5,6,7,8] and to decrease hippocampal long-term potentiation [9]. However, others have found that prenatal stress may also enhance spatial memory [10,11].…”
Section: Introductionmentioning
confidence: 99%